A experiência da solidão a partir do olhar de pessoas idosas do Programa Grupo de Educação na Terceira Idade - RIBEIRO, Simone Correia (Universidade Federal do Pará, 2023)
Based on the elements that contribute to the occurrence of the phenomenon of loneliness in the elderly, this research proposes a reflection on the experience of loneliness from the perspective of elderly people from the Grupo de Educação na Terceira Idade (GETI) Program. The study aims to investigate, based on the various dimensions of loneliness, the social/personal elements that cause the experience of loneliness among elderly people at GETI and, to achieve this objective, we carried out a study with a qualitative approach and the production of data was carried out at from the application of a previously structured interview script, whose questions were directed to the following categories: family life experience, network of social relationships and feeling of loneliness. For the analysis of the data produced, we used the content analysis method, which according to Bardin (2015) refers to a grouping of communication analysis techniques. This analysis technique allows the researcher to observe the different forms of communication that the interviewee emits during the interview. The research was carried out in the municipality of Castanhal, northeast of Pará, with elderly people from GETI, UFPA, Campus de Castanhal. The data were produced between November 2020 and May 2021, totaling 6 (six) subjects interviewed, 1 (one) man and 5 (five) women over 60 years of age. The investigation revealed that, due to the global/current pandemic scenario caused by SARS-CoV-2, the phenomenon of loneliness is more present and has presented itself in its most harmful version in the life of the elderly. Factors such as social distancing, the loss of loved ones and family members, in addition to anxiety, have had harmful impacts on the daily lives of the elderly. It is concluded that the construction of the data highlights the importance and the possibility of reflecting on the dimensions of the loneliness phenomenon in the life of the elderly, as well as on the importance of affective-social relationships in the routine of this public, as a way of providing them with support with the changes required by aging and, consequently, help in experiencing a better quality of life in old age. The importance of the role of public policies that govern the laws of the elderly and guarantee their rights is highlighted. It is important, however, to highlight that society needs to know and value these laws and treat the elderly as active and significant subjects, worthy of enjoying their rights and living in safety. Society, therefore, can provide the advancement of struggles for the rights of the elderly, for the dignity of aging and for compliance with the laws (BETTINELLI; PORTELLA, 2004).